Resultados em e-Learning corporativo - Cardoso, Fernando de Carvalho (2011)
Companies are extending the use of the e-learning in their processes of corporate education, this work began in the quest to answer what are the impacts of implementing e-learning in the educational process in corporations. This work describes a study of the results of the actions of e-learning and the context in which it is inserted on the corporations and society. We study authors were talk about education, corporate education, HR, e-learning and results in corporate and educational activities. We made a qualitative research on companies that use e-learning to understand their impacts. We approach on this thesis the evolution process of the HR professional and their current challenges, what has been done in corporate education and its goals, how e-learning solution has been inserted in corporate education, the state of the art on e-learning and what has been done in the analysis of results in corporate education. We find in the research the main impacts that e-learning has resulted in corporate education: new possibilities for learning, productivity on the training department, financial economics, digital inclusion and return on investment. This study shows that e-learning goes beyond its direct impacts, which is one more movement in support of HR Strategic and enhancement of human capital, it is a means to support classroom education and allows the company to incorporate the change occurring in the cultural world, called Web 2.0 and uphold the new way we relate to knowledge. We found that the learning process is inherent in the educational process, and that e-learning has brought positive results in the learning process. Based on all this work the greatest impact of e-learning in corporate education is the evolution of corporate education as a whole, its reinvention, the evolution of classroom education and also an evolution of the students in their learning style, the HR in the way they develop people and measure their results, and the company create, disseminate and share knowledge